Pediococcus pentosaceus MZF16 Probiotic Strain Prevents In Vitro Cytotoxic Effects of Pseudomonas aeruginosa H103 and Prolongs the Lifespan of Caenorhabditis elegans - Meryem Boujnane; Mohamed Zommiti; Olivier Lesouhaitier; Mounir Ferchichi; Ali Tahrioui; Amine M. Boukerb; Nathalie Connil (Pathogens)
Pseudomonas aeruginosa is an opportunistic pathogenic bacterium, responsible for several life-threatening infections due to its multiple virulence factors and problematic multi-drug resistance, hence the necessity to find alternatives such as competitive probiotics. Pediococcus pentosaceus MZF16 is an LAB strain, isolated from traditional dried meat “Ossban”, with high probiotic potential. Our study investigated the capacity of P. pentosaceus MZF16 to counteract P. aeruginosa H103 using several tests on intestinal cells (analysis of cytotoxicity, inflammation, adhesion/invasion) and on the in vivo Caenorhabditis elegans model. The effect of MZF16 on the quorum sensing of the pathogen was also examined. We found that P. pentosaceus MZF16 was able to reduce H103 cytotoxicity and inflammatory activity and prevented pathogen colonization and translocation across Caco-2/TC7 cells. MZF16 also exerted an anti-virulence effect by attenuating quorum-sensing (QS) molecules and pyoverdine production and extended C. elegans lifespan. The obtained results highlight the potential of P. pentosaceus MZF16 probiotic strain as an anti-Pseudomonas aeruginosa alternative and establish a basis for elucidating the mechanisms of P. pentosaceus MZF16 involved in countering P. aeruginosa virulence.